PERISTIWA 3 MARET 1947 DI PADANG SUMATERA BARAT - Ayu Utari Marwanti; Bedriati Ibrahim; Ridwan Melay (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The event March 3, 1947 was an event that occurred because of a sense of dissatisfaction with the attitude of the government which seemed pro-ally. The purpose of this research was 1) to find out the cause of the events of March 3, 1947, 2) to find out the plans of the events of March 3, 1947, 3) to reveal the chronology of the events of March 3, 1947, 4)to find out the government's settlement in March 3, 1947. Qualitative research methods with historical approaches and data collection techniques in the form of literature, documentation, observation and interviews. The result of this research was that there is a feeling of dissatisfaction with the government's attitude which is not only pro-government, there are also a handful of religious groups which they say are very influenced by the socialist and communist groups and with such dissatisfaction some groups have kidnapped several government figures but it was quickly discovered by the military government regarding the attempted kidnapping and immediately carried out control over the people involved in the incident.Key Words: The event of March 3, West Sumatra